(untitled) (Gragoatá, 2016)
This essay analyzes João Paulo Borges Coelho’s latest novel, Rainhas da Noite (2013), from the perspective of its portrayal of colonial women. My argument begins by recalling Laura Calvacante Padilha’s inspired insights into the representation of voices from pre-colonial traditions in modern African fiction. I then develop and extend Padilha’s work by including voices from the historically more recent colonial past within the fictional repertory of recovered voices. Borges Coelho’s writings indeed allude to spaces and “voices” of African tradition, as Padilha argues. I suggest, however, that it is the memory of the past of Mozambican colonial time, as well as the relation between that past and a present defined by post-independence, that constitutes the axis of aesthetic and social meaning in Rainhas da Noite. The recent past of Portuguese colonial domination permeates Borges Coelho’s novels. —————————————————————————————————- “E tu, que achas tu de tudo isto?”: Mulheres colonas, memória e Pós-Independência em Rainhas da Noite de João Paulo Borges Coelho Este ensaio analisa o último romance de João Paulo Borges Coelho, Rainhas da Noite (2013), da perspetiva da sua representação das mulheres colonas. O meu argumento começa com a invocação do trabalho crítico elaborado por Laura Calvacante Padilha sobre a representação de vozes das tradições pré-coloniais na ficção moderna africana. Pretendo ampliar o trabalho de Padilha ao incluir vozes de um passado colonial historicamente mais recente no interior do repertório ficcional de vozes recuperadas. A escrita de Borges Coelho alude de fato para espaços e “vozes” da tradição africana, como argumenta Padilha. Sugiro, contudo, que é a memória do passado colonial moçambicano assim como a relação entre o passado e o presente definido pelo Pós-Independência, que constitui o eixo do significado estético e social em Rainhas da Noite. O passado recente da dominação colonial portuguesa permeia os romances de Borges Coelho. — Artigo em inglês.